Pengaruh struktur kepemilikan manajerial, debt covenant dan growth opportunities terhadap konservatisme akuntansi - Indah Wulandari; Andreas '; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of managerial ownership structure, debt covenants, and growth opportunities to accounting conservatism. This study used a sample of 53 companies listed in Indonesia Stock Exchange from 2010 to 2012. Samples were selected using purposive sampling method. Data was multiple regresion analysis with software SPSS version 17 (Statistical Product and Service Solution version 17). The data test have been used is a partial hypotesis test (t). The results showed that managerial ownership structure had no effect on accounting conservatism, while debt covenant effect on accounting conservatism and growth opportunities effect on accounting conservatism.Keywords: Managerial Ownership Structure, Debt Covenant, Growth Opportunities